Development of Electronic Module Using Kvisoft Flipbook Maker Application on the Chemical Equilibirium - Wahyuni, Sri Indra; M. Noer, Asmadi; Linda, Roza (Proceedings of the UR International Conference on Educational Sciences, 2018)
The general purpose of this research is to develop e-modules using the Kvisoft Flipbook Maker application on the subject of chemical equilibrium. Specifically this research is aimed at describing the validity of using e-modules on the subject of chemical equilibrium.The method used in this study is the research and development method, with reference to the Plomp model, which consists of three phases, namely the preliminary investigation phase, the prototyping phase and the assessment phase. The results of the analysis showed that the e-module developed using the Kvisoft Flipbook Maker application on the subject of chemical equilibrium was declared valid and feasible to be used in learning activities with the percentage of media experts 94.8%; material expert 88.46%; and practicality test with a teacher response of 95.29%.